The Influence of Islamic Economic Education on the Level of Public Awareness in Managing Finances - Dwi Ayu Widyaningsih; Emilda Sari; Selly Silviawati; Asep Muhammad Adam; Panji Lukito; Majdi Kasheem (Lafadz Jaya Publisher, 2026)
This study aims to analyze the influence of Islamic economic education on the level of public awareness in managing finances. The research method used is descriptive qualitative research with data collection techniques through interviews and observations. The research sample consisted of 20 respondents consisting of the public who are active in Islamic economic activities. The results of the study indicate that Islamic economic education has a significant influence on the level of public awareness in managing finances, which is reflected in several aspects, namely increased awareness of the importance of managing finances in an Islamic manner, increased community ability to manage finances effectively and efficiently, and increased awareness of the importance of zakat and alms to improve community welfare. The conclusion of this study is that Islamic economic education plays an important role in increasing public awareness in managing finances. Therefore, it is recommended for Islamic economic education institutions to improve the quality of economic education delivered to the community.